THE EFFECT OF A STEM APPROACH WITH THE PROBLEM BASED LEARNING MODEL ON COMMUNICATIVE SKILLS AND STUDENT LEARNING OUTCOMES - Umi Kulsum; Slamet Hariyadi; Mochammad Iqbal (ScienceEdu: Jurnal Pendidikan IPA, 2020)
Teaching and learning process can be combined with the existence of skills. There are 4 types of skills that can be needed in the 21st century era. One such skill is the Communicative skill. Communicative skills are learning that emphasizes aspects of communication, interaction, and developing linguistic competencies, as well as language skills (listening, reading, writing, speaking) as a goal to recognize that there is a connection with communication activities in daily life. The learning process can also use a learning approach that is relevant for students so that students can improve student learning outcomes at school. One learning approach that fits the 2013 curriculum is the STEM approach is a learning approach that combines two or more fields of science contained in STEM, namely science, technology, engineering or engineering, and mathematics. Through the STEM approach students are expected to have 2 skills of learning and innovation which include critical thinking, creative, innovative, and able to communicate and collaborate. Thus, learning must be embedded in basic concepts to the development of science and thinking skills.